The Implementation of Liveworksheets in Teaching Basic English Literacy - Arsani, Ni Ketut Ari; Padmadewi, Ni Nyoman; Dewi, Kadek Sintya (English Education Department STKIP Agama Hindu Singaraja, 2025)
This research aimed to investigate the implementation of Liveworksheets in teaching basic English literacy among 7th-grade students. This study used a quasi-experimental research design with a post-test only for both the control group and the experimental group. The population was the seventh-grade students. Two classes were selected as samples, with each class containing 36 and 35 students. IBM Statistics SPSS 26 was used for the analysis of the collected data. The results of the data analysis show that students in the experimental group achieved higher mean scores (M = 81.25) compared to the control group (M = 69.57). In addition, the independent sample t-test results indicate a significant difference between the two groups. Moreover, the results of Cohen’s d effect size with a score of 1.303 indicate a large effect of the influence of Liveworksheets on students’ basic English literacy. The results of this experiment indicate that Liveworksheets affect students’ basic English literacy skills.